2020
DOI: 10.1111/jar.12731
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomized controlled trial of a simplified 5‐step handwashing technique versus a conventional 7‐step handwashing technique among Chinese students with intellectual disabilities

Abstract: Objective To compare the effects of the simplified 5‐step and the conventional 7‐Step hand hygiene programme in a cluster randomized controlled trial among students with intellectual disabilities. Method A total of 472 Chinese students with intellectual disabilities were randomized to either simplified 5‐step or conventional 7‐step hand hygiene programme. Assessments included handwashing technique, cleanliness and sick leave days. Results Handwashing technique scores (g = 0.25, 95% CI [0.18, 0.32]) and hand cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Two studies identified participants with intellectual disability from educational records: an Education and Health Care Plan in place (Grindle et al, 2021), or input from an educational psychologist (Drysdale & Porter‐Armstrong, 2008). The remaining (8/27) studies did not specify how diagnoses were made (Balthazar & Sindberg, 1971; Baran et al, 2013; Dessemontet et al, 2021; Janeslätt & Granlund, 2019; Lee et al, 2017; Lee et al, 2020; McPherson et al, 2017; Roberts‐Tyler et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies identified participants with intellectual disability from educational records: an Education and Health Care Plan in place (Grindle et al, 2021), or input from an educational psychologist (Drysdale & Porter‐Armstrong, 2008). The remaining (8/27) studies did not specify how diagnoses were made (Balthazar & Sindberg, 1971; Baran et al, 2013; Dessemontet et al, 2021; Janeslätt & Granlund, 2019; Lee et al, 2017; Lee et al, 2020; McPherson et al, 2017; Roberts‐Tyler et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (24/27) reported intellectual disability severity explicitly as mild, moderate, severe, or profound, or by providing information about participant's IQ scores. The majority (17/27) included participants with mild, mild–moderate, or moderate intellectual disability (Agbaria, 2020; Bagattoni et al, 2020; Baran et al, 2013; Dessemontet et al, 2021; Drysdale & Porter‐Armstrong, 2008; Hessl et al, 2019; Hong, 2012; Jacques & Townsend, 1998; Janeslätt & Granlund, 2019; Kantner & Clark, 1982; Kostulski et al, 2021; Lee et al, 2017; Lee et al, 2020; Maïano & Erraïs, 2001; McDuffie et al, 2018; Roberts‐Tyler et al, 2020; Wuang & Su, 2013). Seven studies included participants with moderate–severe or severe intellectual disability (Balthazar & Sindberg, 1971; Grindle et al, 2021; Lanfranchi et al, 2015; Litrownik et al, 1978; Sepúlveda & Heinze, 2013), two of which were published from the same cohort with an average DQ of 30 (Saint‐Georges et al, 2020; Tanet et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations